Dynamic model of A DC-DC quasi-Z-source converter (q-ZSC) - Muhammad Ado; Awang Jusoh; Abdulhamid Usman Mutawakkil; Tole Sutikno (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Two quasi-Z-source DC-DC converters (q-ZSCs) with buck-boost converter gain were recently proposed. The converters have advantages of continuous gain curve, higher gain magnitude and buck-boost operation at efficient duty ratio range when compared with existing q-ZSCs. Accurate dynamic models of these converters are needed for global and detailed overview by understanding their operation limits and effects of components sizes. A dynamic model of one of these converters is proposed here by first deriving the gain equation, state equations and state space model. A generalized small signal model was also derived before localizing it to this topology. The transfer functions (TF) were all derived, the poles and zeros analyzed with the boundaries for stable operations presented and discussed. Some of the findings include existence of right-hand plane (RHP) zero in the duty ratio to output capacitor voltage TF. This is common to the Z-source and quasi-Z-source topologies and implies control limitations. Parasitic resistances of the capacitors and inductors affect the nature and positions of the poles and zeros. It was also found and verified that rather than symmetric components, use of carefully selected smaller asymmetric components L1 and C1 produces less parasitic voltage drop, higher output voltage and current under the same conditions, thus better efficiency and performance at reduced cost, size and weight.